2004
DOI: 10.1158/0008-5472.can-04-1169
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Morphological and Biochemical Apoptosis following Prolonged Mitotic Blockage by Halichondrin B Macrocyclic Ketone Analog E7389

Abstract: E7389, a macrocyclic ketone analog of the marine natural product halichondrin B, currently is undergoing clinical trials for cancer. This fully synthetic agent exerts its highly potent in vitro and in vivo anticancer effects via tubulin-based antimitotic mechanisms, which are similar or identical to those of parental halichondrin B. In an attempt to understand the impressive potency of E7389 in animal models of human cancer, its ability to induce apoptosis following prolonged mitotic blockage was evaluated. Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
172
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 236 publications
(184 citation statements)
references
References 33 publications
6
172
0
1
Order By: Relevance
“…Halichondrins are noncompetitive inhibitors of vinca alkaloids that occupy the vinca-binding domain on tubulin, suppress the growth of microtubules, and inhibit polymerization, thereby inducing cell cycle arrest and apoptosis (75). The halichondrin analog erubilin mesylate (also known as E7389, ER-086526, and NSC 707389) inhibits the polymerization of purified tubulin more potently than the parent compound halichondrin B (76).…”
Section: Halichondrin B Analog Erubilin Mesylatementioning
confidence: 99%
“…Halichondrins are noncompetitive inhibitors of vinca alkaloids that occupy the vinca-binding domain on tubulin, suppress the growth of microtubules, and inhibit polymerization, thereby inducing cell cycle arrest and apoptosis (75). The halichondrin analog erubilin mesylate (also known as E7389, ER-086526, and NSC 707389) inhibits the polymerization of purified tubulin more potently than the parent compound halichondrin B (76).…”
Section: Halichondrin B Analog Erubilin Mesylatementioning
confidence: 99%
“…Satraplatin (JM-216), an oral platinum compound, is currently being evaluated in a large international trial (SPARC), in combination with prednisolone as second-line treatment after docetaxel. Novel tubulin binding drugs such as the epothilone B analogue, ixabepilone (BMS-247550) (Galsky et al, 2005) and the halichondrin B analogue, E7389 (Kuznetsov et al, 2004), have demonstrated promise in the post-docetaxel setting and clinical trials are ongoing.…”
Section: Current Treatmentsmentioning
confidence: 99%
“…Yondelis, isolated from Ecteinascidia turbinate, was approved for clinical use in metastatic soft tissue carcinoma and ovarian cancer in 2009 in Europe [5]. Another approved marine-based drug is Halaven, an analogue of halichondrin B, extracted from the sea sponge Halichondria okadai [11], and was approved for the treatment of metastatic breast cancer in 2010 from FDA. Besides these three marine anti-cancer agents currently being marketed, several marine products and their derivatives such as aplidin, bryostatin-1, and zalypsis are undergoing phase II and III clinical trials [5].…”
Section: Introductionmentioning
confidence: 99%